2022
DOI: 10.1002/tpg2.20261
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors underlying anaerobic germination in rice: Genome‐wide association study and transcriptomic analysis

Abstract: The success of rice (Oryza sativa L.) germination and survival under submerged conditions is mainly determined by the rapid growth of the coleoptile to reach the water surface. Previous reports have shown the presence of genetic variability within rice accessions in the levels of flooding tolerance during germination or anaerobic germination (AG). Although many studies have focused on the physiological mechanisms of oxygen stress, few studies have explored the breadth of natural variation in AG tolerance‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…In the region of qPP4 , the annotated gene was CTB2 ( Figure 6 a,b). The CTB2 gene, which encodes a UDP-glucose sterol glucosyltransferase, is responsible for cold tolerance in rice at the booting stage [ 35 ]. To understand how the CTB2 sequence may affect the PP phenotype, we analyzed the SNPs in the genomic coding region of CTB2 across the 302 varieties, which revealed five major haplotypes, two SNPs in the coding region and seven SNPs in the intron region ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the region of qPP4 , the annotated gene was CTB2 ( Figure 6 a,b). The CTB2 gene, which encodes a UDP-glucose sterol glucosyltransferase, is responsible for cold tolerance in rice at the booting stage [ 35 ]. To understand how the CTB2 sequence may affect the PP phenotype, we analyzed the SNPs in the genomic coding region of CTB2 across the 302 varieties, which revealed five major haplotypes, two SNPs in the coding region and seven SNPs in the intron region ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of each accession were harvested individually after maturity. The harvested seeds were dried in a hot air dryer at 37 °C for 5 days and then stored at room temperature for three months [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although earlier research has primarily delved into the physiological aspects of oxygen stress, only few investigations have explored the broad spectrum of natural variation in traits related to anaerobic germination tolerance in rice. Thapa et al (2022) conducted a GWAS analysis on a rice diversity panel comprising 241 accessions, revealing 30 significant marker-trait associations (MTAs). Among these MTAs, 14 colocalized with previously detected genes linked to anaerobic germination tolerance, while 16 were novel discoveries.…”
Section: Anaerobic Germination Tolerancementioning
confidence: 99%
“…Thapa et al. (2022) conducted a GWAS analysis on a rice diversity panel comprising 241 accessions, revealing 30 significant marker‐trait associations (MTAs). Among these MTAs, 14 colocalized with previously detected genes linked to anaerobic germination tolerance, while 16 were novel discoveries.…”
Section: Anaerobic Germination Tolerancementioning
confidence: 99%
“…Many studies on QTL mapping and genome wide association studies (GWAS) on AG tolerance in rice have been reported [10][11][12][13][14][15][16][17][18][19][20][21][22]. Notably, a gene underlying one of the QTLs, qAG-9-2, has been cloned as trehalose-6-phosphate-phosphatase (OsTPP7), which is involved in starch mobilization during germination [23].…”
Section: Introductionmentioning
confidence: 99%